2013
DOI: 10.1111/j.1559-1816.2013.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for physical activity in young adults with physical disabilities during a rehabilitation stay: a longitudinal test of self‐determination theory

Abstract: We tested a self-determination theory (SDT) process model during a 3 week physical activity rehabilitation stay among young adults with a physical disability (N = 44, Mage = 24.7, SD = 5.1). As hypothesized, perceived autonomy support positively predicted needs satisfaction at the end of the stay (r = .38, p < .01). Further, needs satisfaction was positively linked to changes in autonomous motivation for physical activity (r = .47, p < .01). Both changes in autonomous motivation and self-efficacy were associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 61 publications
3
25
0
1
Order By: Relevance
“…et al, 2012). A number of more specific studies that have examined self-determination in a sample of people with a disability found similarly positive outcomes (Perreault & Vallerand, 2007;Saebu et al, 2013).…”
Section: The Problemmentioning
confidence: 98%
“…et al, 2012). A number of more specific studies that have examined self-determination in a sample of people with a disability found similarly positive outcomes (Perreault & Vallerand, 2007;Saebu et al, 2013).…”
Section: The Problemmentioning
confidence: 98%
“…A sample item is: "How confident are you that you can do aerobic exercise such as walking, swimming, or bicycling 3 to 4 times each week?" Responses were given on a 10-point Likert-type scale, ranging from not at all confident (1) to totally confident (10). The scale has been tested for validity in a sample with 478 subjects with chronic diseases; internal consistency was 0.83, and test-retest reliability was 0.86 (34).…”
Section: Assessmentsmentioning
confidence: 99%
“…Controlled motivation is derived from external sources, such as physicians, trainers or media (8), while autonomous motivation is derived from oneself across 3 basic psychological needs: autonomy, relatedness and competence (9). Recent research has shown the importance of autonomous motivation for adherence to physical activity (8), and that it is associated with increased activity in people with physical disabilities (10). It is also noteworthy that maintenance of behaviours over time requires autonomous motivation for that behaviour (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cross-sectional and longitudinal studies in healthcare settings support this notion that is, perceived autonomy support from healthcare providers is associated with autonomous motivation, which in turn is related to rehabilitation adherence [18][19][20][21][22]. For example, in a sample of 115 post-surgery anterior cruciate ligament patients, Chan et al [18] investigated the relationship between physiotherapists' autonomy-supportive behaviors, patients' motivation for rehabilitation, and patients' post-surgery rehabilitation adherence.…”
mentioning
confidence: 99%